The Explanation of the Eternal Punishment for Murderer Who Is Muʾmin in the 93rd Verse of Sūrat al_Nisāʼ with a Look to the Maxim: “the Suspension of Hukm in the Attribute Which Implies to the Reason” - Majid Zarei; Hamed Dezhabad (آموزه‌های قرآنی, 2019)
There are two major currents in the explanation of the eternal problem among the Quran exegetes. Some believe that the eternal in hell means immortality and some others accept that it means that a long stop and not immortality. Majority of the Quran exegetes have accepted the first opinion but it faces challenges. One of the problems which should mention for this idea is the argument (reason) being extracted from the 93rd verse of sūrat al_Nisāʼ. This verse has used the general (ʿām) word for the murderer which it includes the believers especially the address in the preceding and next verses has been delivered to the believers. Whereas, according to the Islamic teachings such as shafa'ah (intercession) traditions, the believers will never remain in the hell forever. With applying the maxim “the suspension of hukm in the attribute which implies to the reason” which has been propounded in ilm usul al_fiqh (the Principles of Islamic jurisprudence), meanwhile removing this contradiction, the present research will show that the faith (iman) attribute of the killed has been regarded in the hukm (ruling) and the killing intentionally and hostilely for the faith of the killed has been paid attention which it has no harmony with the soul of faith. It will be clear that not only such punishment from God who is just and kind for this killing is not counted cruelty and it has not prohibited by intellect and at the end it is counted wisdom (al-hikmah) but also the ruling of eternal living of these groups in the hell is in agreement with other appropriate verses and this verse is not counted an exception for the eternal hukm (ruling), that is, the punishment being everlasting.